Divisions, Sub-Divisions and their ethnic groups in West Cameroon (also in French, post independence) (Colonial Letters and the Contact of Knowledges, 1966)
This file contains colonial letters on Divisions, Sub-Divisions and their ethnic groups in West Cameroon
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies